Information literacy skills of Greek high-school students: results of an empirical survey - Malliari, Afrodite; Togia, Aspasia; Korobili, Stella; Nitsos, Ilias (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
In this paper we explore information literacy skill levels among high-school students and the need to incorporate information literacy in the education process in Greek secondary education. More specifically, a survey was conducted among first year high-school students in Thessaloniki, Greece. The procedure provided 344 usable questionnaires. The results of the study suggest that first year high-school students in Greece are accustomed to using computers in their daily live, they use the Internet to satisfy personal needs, but they have problems in locating and evaluating information for school work. The findings of the present study clearly suggest the need to embed information literacy instruction into secondary education, and also the need to create an online information literacy tutorial. Therefore, an online information literacy tutorial is being developed in line with Big6 model and constructivist approaches.